A strategic plan for Evergreen Employees Multi-Purpose Cooperative (EEMPC) - Exiomo, Charmavirlou A. (School of Management, University of the Philippines Mindanao, 2007)
A cooperative is a duly registered association of persons, who have voluntarily joined to achieve a lawful common social or economic end in accordance with universally accepted cooperative principle. It is for this reason that Evergreen Employees Multi-Purpose Cooperative (EEMPC was created. Cooperated on March 1982 by virtue of Republic Act 6928, EEMPC was registered as a primary, multi-purpose, non-agricultural cooperative with Cooperative Development Authority (CDA). From humble beginnings, EEMPC rose to become one of the biggest coops in Lapanday Group of Companies with membership base of 514 and total asset of Php 16.06 Million as of December 2005.With this achievement, the author was inspired to provide EEMPC with a strategic plan to become more sustainable aside from helping them face the challenges in 2007 and the years to come. By doing this, the author applied various tools and techniques in coming up with the data and information presented in this strategic paper such as interview, survey, focus group discussion, internal and external factors evaluation, P.E.S.T., S.W.O.T. and QSPM matrices. Data related to the company's internal environment include cooperative profile, operational practices, organizational structure and financial standing. External data such as industry and market profile, competitors, Philippine, particularly Davao situationer, policies and regulations affecting cooperatives and economic trends were gathered through interviews and various websites. The external scanning showed that the cooperative has a strong potential to meet the opportunities and has the capability to ward off the threats it faces. The internal scanning on the other hand showed that EEMPC is capitalizing on its strong officers and leaders, high capitalization and profitability. However, its weaknesses lie generally on marketing and low utilization of assets. As noted in the survey conducted by the author to its members, investments and projects are the first area they would like to improve in the next years. With these outcomes, the author was able to develop strategic alternatives that resulted in the identification of the cooperative's need to empower their general assembly, develop new markets and modify their existing products. These strategies were then translated into specific and workable activities of EEMPC. Countered by maximization of the efforts and use of its available resources and potentials, the assessment and analysis of these issues also paved way for the conception of strategies for implementation. These implementation policies include a) continuous education for all the members; b) succession planning; c) construction of EEMPC kiosk; d) offering of seasonal credit line; e) referral incentives; f) increase loanable amount and payment terms, and; g) hiring of one full-time Coop Manager. To evaluate if the above strategies were fully implemented, four indicators were set, that is, increase in net surplus, number of members, and patronage and satisfactory rate during evaluation. Moreover, it is must that information systems will be in placed. This will not only provide the coop with basic information but at the same time monitor the financial standing of the coop.